Clinical and spirometric variables are better predictors of COPD exacerbations than routine blood biomarkers. (September 2020) - Nuñez, Alexa; Marras, Viviana; Harlander, Matevz; Mekov, Evgeni; Turel, Matjaz; Petkov, Rossen; Lestan, David; Yanev, Nikolay; Negri, Silvia; Barrecheguren, Miriam; Pirina, Pietro; Miravitlles, Marc; et al.
Abstract: Background: Understanding the risk factors for exacerbations of COPD may help provide a more personalised approach to exacerbation prevention. Method: Observational, prospective, international, multicentre study aimed at identifying risk factors for exacerbations of COPD. Clinical variables, lung function and CAT scores were collected at baseline. In addition, routine blood biomarkers were also obtained, and patients were followed for 12 months. Results: A total of 326 patients were included. Of these, 155 (47.5%) presented at least one exacerbation. The median time to the first exacerbation was 147 days. Exacerbators had more respiratory symptoms, more impairment in FEV1(%), FVC(%) and a worse CAT score. Regarding biomarkers, only C-reactive protein was significantly higher in exacerbators (2.8 (standard deviation (SD):3.8) mg/dL vs. 1.9 (SD:2.6) mg/dL; p = 0.037). In multivariate analysis, only CAT scores, FEV1(%) and previous exacerbations were significantly associated with having an exacerbation during follow-up. In the equation of risk, patients with a CAT score ≥15, FEV1(%) <55% and at least one exacerbation the previous year had a probability of 76% of having an exacerbation during the next year, compared with 17% in patients who had none of the previous variables. No biomarkers showed a significant association in multivariate analysis. Conclusions: Less than half of the patients presented an exacerbation during the one-year follow-up. CAT scores, FEV1(%) and previous exacerbations were the only variables associated with increased risk of exacerbations. Routine biomarkers did not provide additional information to evaluate the risk of exacerbations. Highlights: Approximately half of the COPD patients had an exacerbation during one-year follow-up. CAT, FEV1(%) and previous exacerbations were predictive for future exacerbations. No routine blood biomarker provided additional predictive value.